Jungian Archetypes and the Confluence of Anima and Animus in Heart of Darkness - Muhammad Yousaf Khan; Nasir Jamal Khattak (University of Chitral Journal of Linguistics and Literature, 2022)
This paper discusses Carl Jung’s theory of individuation by exploring the archetypes of anima and animus as portrayed in Conrad’s Heart of Darkness. Individuation is a process of integrating the unconscious contents of the psyche into the conscious. This is symbolized by Marlow’s encounter with the enigmatic Kurtz and the two women related to him. Marlow’s development from confronting his shadow, symbolized in Kurtz, to wrestling with his anima, embodied in Kurtz’s mistress and the white Intended, explains the complex interaction between the two halves of his psyche—the conscious and the unconscious. Through the framework of Jungian analytical psychology, we dig into how Marlow’s psychological development reflects the confluence of anima and animus, underscoring the transformative influence of internalizing these archetypal forces.